Abnormal Coronary Artery Origines and Sudden Death Main Left Coronary Artery Abnormal Origin with a Case - Melez, Deniz Oğuzhan; Turan, Arzu Akçay; Şahin, Esat; Karayel, Ferah; Üzün, İbrahim (The Bulletin of Legal Medicine, 2008)
The deaths originating from cardiovascular diseases are the most important causes of sudden death (90%). According to the mortality statistics, 300.000-400.000 person dies because of sudden cardiac death every year in the United States. However, the atherosclerotic coronary diseases are the major cause of sudden cardiac death in the entire world at the adult ages, anatomic abnormalities of coronary arteries may cause sudden deaths in the young especially while training and has no medical cardiac history before. The abnormalities of coronary arteries which coronary passes through the aorta and pulmonary arteries and the single or both arteries originating from the right sinus have the highest risk of sudden death. In this study we present a 21 year old young man, died suddenly after training, who has no specific symptoms or diagnosis before. In the autopsy, left main coronary artery, abnormally originated from the right sinus and passes through the aorta and pulmonary arteries is founded. The anatomic and pathologic features of the high risk coronary artery anomalies are reviewed with the findings of the case. Key words: Coronary artery anomaly, sudden cardiac death, autopsy